Adherence to Clinical Practice Guidelines (CPG) management of dengue infection in adults (revised 2nd edition) - Abd. Rahman, M.; Zaki, R.A.; Sarimin, R.; Ariff, M.I.; Suli, Z.; Mahmud, M.; Bee, K.H.; Anthonysamy, C.; Rahim, A.A.; Gill, B.S.; Deva, S.R.; Sani, A.F.A.; et al. (Public Library of Science, 2017)
The Malaysian Dengue Clinical Practice Guidelines (CPG) have been developed to provide evidence-based guidance in the management of dengue infections. The use of these guidelines is essential to ensure its recommendations are being practiced. However, the adherence to the guidelines for management of dengue (revised 2nd edition) by healthcare providers still remains unknown. Therefore, the aim of this study was to evaluate the proportion among healthcare providers that adhere to this Dengue CPG. A retrospective cohort study of dengue cases registered from 1 January 2014 to 1 June 2015 was conducted in public hospitals and health clinics in Selangor, Putrajaya and Kuala Lumpur. Adherence to the CPG recommendations were recorded by reviewing patients’ case notes. Overall proportion of adherence in clinical components of the recommendation were (7.1 to 100.0% versus 7.7 to 73.8%) in history taking, (6.7 to 100.0% versus 12.3 to 60.0%) in physical examinations, (18.4 to 100.0% versus 23.1 to 83.2%) in assessment of warning signs, (0.6 to 100.0% versus 12.3 to 87.7%) in assessment of haemodynamic status, (60.0 to 100.0% versus 27.7 to 40.0%) in diagnosis, (46.6 to 80.0% versus 52.3%) in case notifications, (73.2 to 100.0% versus 89.2 to 96.9%) in performing specific laboratory investigations and (7.9 to 100.0% versus 21.5%) in monitoring, for outpatient versus inpatient, respectively. Adherence trends were demonstrated to be higher in hospital settings compared to outpatient settings. Adherence to this Dengue CPG varies widely with overall good clinical outcomes observed.